1305 nm Few‐Layer MoTe2‐on‐Silicon Laser‐Like Emission (Laser Photonics Rev. 12(6)/2018). Issue 6 (14th June 2018) - Fang, Hanlin; Liu, Jin; Li, Hongji; Zhou, Lidan; Liu, Lin; Li, Juntao; Wang, Xuehua; Krauss, Thomas F.; Wang, Yue
Abstract : 2D‐On‐Silicon Devices In article number1800015, Juntao Li and co‐workers demonstrate optically pumped silicon laser‐like operation using few‐layer MoTe2 gain material on an L3 silicon photonic crystal nanocavity. The device operates in the center of the "O‐band" of optical communications, at room temperature and with low threshold power. This achievement represents an important step towards integrating active light sources into silicon photonics in a scalable fashion.